Modeling bidirectional transcription using silkmoth chorion gene promoters. - Lecanidou, R; Papantonis, A (2010)
Bidirectional transcription is an interesting feature of eukaryotic genomes; yet not all aspects of its mechanism are understood. Silkmoth choriogenesis is a model system for studying transcriptional regulation at the initiation level. As chorion genes comprise a large group of divergently transcribed gene pairs, we are presented with the possibility of investigating the intricacies of bidirectional transcription. Their well characterized 5' regulatory regions and expression profiles lay the foundation for investigating protein:protein and protein:DNA interactions, and RNA polymerase function during oocyte development. In this article we summarize current knowledge on chorion gene regulation and propose an approach to modeling bidirectional transcription using chorion promoters.